A Single-Goal Fiber Intervention Does Not Compromise Nutritional Intake During Pregnancy. (29th May 2020) - Herman, Amy; Hand, Lauren; Sullivan, Debra; Hull, Holly
Abstract: Objectives: This study evaluated the effects of a single-goal (SG) vs. multiple goal (MG) intervention on food group and nutrient intake during pregnancy. Methods: Two separate pilot studies randomized women to an intervention (SG or MG) or usual care (UC; n  = 19 combined) aiming to prevent excessive gestational weight gain. Each group met weekly with a registered dietitian. In the MG study ( n  = 21), women were counseled on healthy eating and exercise. In the SG study ( n  = 16), weekly lessons focused only on increasing fiber intake (≥30 g/day); mention of all other nutrients including calories was intentionally omitted. In both studies, multiple-pass 24-hour dietary recalls were collected at baseline and end of study and analyzed with Nutrient Data System for Research (NDS-R). Diet quality was calculated using the Alternative Healthy Eating Index for Pregnancy (AHEI-P). ANOVA determined between group differences for micronutrient intake and food group servings. Paired t-tests determined within group differences in diet quality. Nutrients from dietary supplements were not included in analyses. Results: All analyses reported are for data from the end of the studies. For nutrients of concern during pregnancy, when compared to the MG group, the SG group had greater calcium intake ( P  = 0.04). No between group difference was found for folate, iron, choline, or DHA. For food groups, when compared to the MG group, the SG group had greater fruit and whole grain intake ( P  < 0.05). No between group difference was found for protein, vegetables, nuts and legumes, or sugar-sweetened beverages ( P > 0.05). No differences were found between SG and UC or MG and UC for any nutrients or food groups. AHEI-P score increased in the SG group during the study ( P  = 0.01), but not in the MG or UC groups ( P > 0.05). Conclusions: An intervention focused solely on increasing fiber intake did not cause decreased intake in other foods groups or nutrients. Only the SG group increased diet quality throughout the study. These data suggest focusing on fiber only did not create unintended negative dietary consequences and may be an effective simple message intervention for diet improvement. Larger studies are needed to further explore these results. Funding Sources: This study was supported by a NIH Clinical and Translational Science Award and the Kansas City Area Life Sciences Institute.